Low-energy constraints on photoelectron spectra measured from liquid water and aqueous solutions. Issue 14 (12th March 2021) - Malerz, Sebastian; Trinter, Florian; Hergenhahn, Uwe; Ghrist, Aaron; Ali, Hebatallah; Nicolas, Christophe; Saak, Clara-Magdalena; Richter, Clemens; Hartweg, Sebastian; Nahon, Laurent; Lee, Chin; Goy, Claudia; et al.
Abstract : We report on the effects of electron collision and indirect ionization processes on the photoemission spectra of liquid water, specifically at photoexcitation and electron kinetic energies well below 30 eV. Abstract : We report on the effects of electron collision and indirect ionization processes, occurring at photoexcitation and electron kinetic energies well below 30 eV, on the photoemission spectra of liquid water. We show that the nascent photoelectron spectrum and, hence, the inferred electron binding energy can only be accurately determined if electron energies are large enough that cross sections for quasi-elastic scattering processes, such as vibrational excitation, are negligible. Otherwise, quasi-elastic scattering leads to strong, down-to-few-meV kinetic energy scattering losses from the direct photoelectron features, which manifest in severely distorted intrinsic photoelectron peak shapes. The associated cross-over point from predominant (known) electronically inelastic to quasi-elastic scattering seems to arise at surprisingly large electron kinetic energies, of approximately 10–14 eV. Concomitantly, we present evidence for the onset of indirect, autoionization phenomena (occurring via superexcited states) within a few eV of the primary and secondary ionization thresholds. These processes are inferred to compete with the direct ionization channels and primarily produce low-energy photoelectrons at photon and electron impact excitation energies below ∼15 eV. Our results highlight that vibrational inelastic electron scattering processes and neutral photoexcitation and autoionization channels become increasingly important when photon and electron kinetic energies are decreased towards the ionization threshold. Correspondingly, we show that for neat water and aqueous solutions, great care must be taken when quantitatively analyzing photoelectron spectra measured too close to the ionization threshold. Such care is essential for the accurate determination of solvent and solute ionization energies as well as photoelectron branching ratios and peak magnitudes.